Threats and the active protection of birds in a riverbed: postulates for the strategy of the preservation of the middle Vistula River avifauna - Dariusz Bukaciński; Monika Bukacińska; Arkadiusz Buczyński (Studia Ecologiae et Bioethicae)
Over the past 34 years, threats to Charadriiform birds inhabiting islands in the Vistula riverbed, mainly gulls, terns and plovers, have changed considerably. While in 1985-1994 the main risks for their breeding were found to be flood waters, predation by the hooded crow Corvus corone cornix and the Eurasian magpie Pica pica, as well as, locally, uncontrolled livestock grazing, in 2005-2014 they were primarily predation pressure from the American mink Neovision vision and the red fox Vulpes vulpes and massive outbreaks of black flies Simuliidae. These threats led to a reproductive outcome of nearly zero and increased the mortality of adults in their breeding areas. As a result, there was a sharp decline in numbers of the majority of gull, tern and plover species nesting there. In 2015-2018, apart from mammalian predation, key threats included the pressure of feral cats and dogs and the growing presence of people on the islands. In a situation that may lead to the extinction of first the mew gull, Larus canus, and later other species of birds, in 2005-2006, we began the active protection of endangered species on the middle Vistula River islands. This effort included (a) reducing the number of American minks and red foxes, (b) neutralising the presence of predators and livestock at the nesting sites with electric fences and the use of incubators and dummy eggs and (c) restoration of the nesting habitat, as well as, in the case of mew gulls, (d) increasing the genetic diversity within colonies. The most important demand is the conducting of the active protective measures in a comprehensive way and continuously for at least five years (until 2023), optimally throughout the decade (2019--2028). In addition, it will be also necessary to carry out wildlife monitoring in this area. The other important task for the coming years will be to oppose plans for extensive engineering in the middle section of the river, which will irreversibly destroy this unique ecosystem.